Membangun sistem Evaluasi yang Humanis dan Adaptif Melalui Pengembangan Teknik Tes dan Non Tes Pada Pembelajaaran PAI di SMPN 02 Danau Kembar - Sartika; Khadijah; Remiswal (Jurnal Ilmu Pendidikan, 2026)
Learning evaluation is an essential component in determining the success of the educational process, particularly in Islamic Religious Education (PAI). However, evaluation practices in many educational institutions remain predominantly focused on test-based assessments that emphasize cognitive achievement, thereby failing to comprehensively measure students' affective, spiritual, and psychomotor development. This condition reflects a gap between the ideal objectives of PAI, which prioritize character building and moral development, and the reality of assessment practices that largely concentrate on academic performance. This study aims to analyze how the development of test and non-test assessment techniques can contribute to establishing a more humanistic and adaptive evaluation system in Islamic Religious Education. The study employs a qualitative approach*using the library research method by examining relevant books, national and international scholarly articles, and educational policy documents. Data were analyzed through data reduction, data display, interpretation, and descriptive-analytical conclusion drawing. The findings indicate that integrating test and non-test assessment techniques creates a more comprehensive, objective, authentic, and student-centered evaluation system. While test techniques effectively measure cognitive achievement, non-test techniques—including observation, portfolios, self-assessment, peer assessment, reflective journals, and interviews—provide a deeper evaluation of students' character, religious attitudes, and worship practices. A humanistic evaluation approach offers constructive feedback, appreciates individual differences, and promotes meaningful, inclusive learning experiences. Therefore, integrating test and non-test assessment techniques represents an effective strategy for developing an adaptive evaluation system that supports the holistic goals of Islamic education and aligns with contemporary educational demands. These findings are consistent with recent studies highlighting the importance of authentic assessment in integrating cognitive, affective, and psychomotor competencies within PAI learning.